PENGEMBANGAN BAHAN AJAR BERBASIS SAINTIFIK PADA TEMA CUACA DI KELAS III SEKOLAH DASAR - Nurmairina, Dinda; Dinda Arianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: (1) To produce the development of scientific-based teaching materials on the theme of weather in grade III of elementary school. (2) To analyze the feasibility of scientific-based teaching materials that will be developed on the theme of weather in grade III of elementary school. Which is based on the lack of student response and student interest in reading during the learning process, this causes difficulties in understanding integrated thematic learning. This study is a type of Research and Development (R&D) research. This study was developed using five steps of the ADDIE development model, including: 1) Analyze, 2) Design 3) Development, 4) Implementation, 5) Evaluation. Data collection techniques used were interviews, observations and questionnaires. Quantitative and qualitative data were analyzed using a Likert scale. This study produced scientific-based teaching materials on the theme of weather in grade III of elementary school with the material "Weather". Based on the validation that has been done by the material expert, it produces a score of 49 with a percentage of 89% with the category of "very feasible", the media expert produces a score of 50 with a percentage of 100% with the category of "very feasible" and practicality produces a score of 33 with a percentage of 94% with the category of "very feasible". The validation results show that the learning media product is feasible to be tested on students. The results of the field trial produced a score of 1,149 with a percentage of 83, with the category of "very feasible". Thus, the scientific-based teaching material product on the theme of weather in grade III of elementary school made by the researcher is feasible to be used in the ongoing learning process.